Impact of Dhap Residue on the Performance of Some Selected Winter Vegetables - Mondal, Asit Baran; Ahmed, Mohammad Bashir; Mannan, Md Abdul (International Journal of Sustainable Agricultural Research, 2022)
The experiment was conducted to evaluate the performance of dhap residue and nutrient sources on the growth and yield of red amaranth, radish and garlic during the period from October, 2013 to February 2014 and October, 2014 to February 2015 at Gopalganj district in Bangladesh. The single factor experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. There were eight treatments viz. control (without organic and inorganic fertilizer), cowdung, recommended dose of NPK, 50% cowdung + 50% recommended dose of NPK, dhap residue, dhap residue + cowdung, dhap residue + recommended dose of NPK, dhap residue +50% cowdung +50% recommended dose of NPK. Dhap residue significantly influences the growth and yield of all three crops i.e red amaranth, radish and garlic. In respect of red amaranth, the tallest plant (43.70 cm and 42.37 cm, respectively) and maximum number of leaves (33.00 and 33.33, respectively) per plant as well as yield (20.88 and 21.32 t ha-1, respectively) were observed from dhap residue + 50% cow dung + 50% recommended dose of NPK which was significantly similar to dhap residue + recommended dose of NPK in both the years. Similar results were also observed in radish for root growth and in bulb production of garlic. From economic consideration, the application of dhap residue + 50% cow dung + 50% recommended dose of NPK fertilizers were suitable for growth and yield as well as cost effective for red amaranth, radish and garlic production under the climatic conditions in Gopalganj district of Bangladesh.